Modelling of Germanium-Based Perovskite Solar Cell for Different Hole Transport Materials and Defect Density - Buruhanutheen, Nurul Afiqah; Abdullah, Ahmad Sharmi; Ibrahim, Mohd Halim Irwan; Ahmad, Fauzan; Ibrahim, Mohd Haniff (Photonics Letters of Poland, 2023)
The performance of four distinct materials (organic and inorganic) was simulated and analyzed as hole transport layer (HTL) in the design of germanium (Ge)-based Perovskite Solar Cell (PSC). A 1-dimensional numerical software (SCAPS 1-D) has been applied to simulate the HTL candidates: spiro-OMeTAD, PTAA, nickel oxide (NiO), and copper (I) thiocyanate (CuSCN), with tin (IV) dioxide (SnO2) as the electron transport layer (ETL). The thickness of the methylammonium germanium iodide (CH3NH3GeI3) absorber was varied from 300 nm to 1100 nm, and the highest simulated power conversion efficiency was achieved at a thickness of 800 nm for all HTL candidates. It was observed that the inorganic CuSCN outperformed its counterparts with a power conversion efficiency (PCE) of 25.38%. The effect of the perovskite absorber’s defect density was investigated, and ultimately, it was demonstrated that this value is disproportionately related to the PCE. A reduction of nearly 98% in PCE was recorded when the defect density increased from 1x1014 cm-3 to 1x1020 cm-3. Additionally, for a constant ETL thickness of 80 nm, it was revealed that the PCE would decrease slightly, ranging from 0.1% to 0.3%, with an increase in HTL thickness from 50 nm to 300 nm. Comparing the PCE of our current work with published reports further justifies its competitiveness. Full Text: PDF References W.R. Becquerel, "Becquerel Photovoltaic Effect in Binary Compounds", J. Chem. Phys. 32, 1505 (1960). CrossRef A. Kojima, K. Teshima, Y. Shirai, T. Miyasaka, "Organometal Halide Perovskites as Visible-Light Sensitizers for Photovoltaic Cells", J. Am. Chem. Soc. 131, 6050 (2009). CrossRef M.M. Salah, K.M. Hassan, M. Abouelatta, A. Shaker, "A comparative study of different ETMs in perovskite solar cell with inorganic copper iodide as HTM", Optik 178, 958 (2019). CrossRef S. Rai, B. Pandey, A. Garg, D. Dwivedi, "Hole transporting layer optimization for an efficient lead-free double perovskite solar cell by numerical simulation", Opt. Mater, 121, 111645 (2021). CrossRef H. Liangsheng, Z. Min, S. Yubao, M. Xinxia, W. Jiang, Z. Qunzhi, F, Zaiguo, L. Yihao, H. Guoyu, L. Tong, "Tin-based perovskite solar cells: Further improve the performance of the electron transport layer-free structure by device simulation", Sol. Energy, 230, 345 (2021). CrossRef K. Fatema, M. Arefin, "Enhancing the efficiency of Pb-based and Sn-based perovskite solar cell by applying different ETL and HTL using SCAPS-ID", Opt. Mater. 125, 112036 (2022). CrossRef P. Patel, "Device simulation of highly efficient eco-friendly CH3NH3SnI3 perovskite solar cell", Sci. Rep., 11, 3082 (2021). CrossRef P. Roy, Y. Raoui, A. Khare, "Design and simulation of efficient tin based perovskite solar cells through optimization of selective layers: Theoretical insights", Opt. Mater., 125, 112057 (2022). CrossRef A.I. Azmi, M.Y. Mohd Noor, M.H.I. Ibrahim, F. Ahmad, M.H. Ibrahim, "A Numerical Simulation of Transport Layer Thickness Effect in Tin-Based Perovskite Solar Cell", JJEE, 8, 355 (2022). CrossRef A.A. Kanoun, M.B. Kanoun, A.E. Merad, S. Goumri-Said, "Toward development of high-performance perovskite solar cells based on CH3NH3GeI3 using computational approach", Sol. Energy, 182, 237 (2019). CrossRef A. Hima, N. Lakhdar, "Enhancement of efficiency and stability of CH3NH3GeI3 solar cells with CuSbS2", Opt. Mater., 99, 109607 (2020). CrossRef S.T. Jan, M. Noman, "Influence of layer thickness, defect density, doping concentration, interface defects, work function, working temperature and reflecting coating on lead-free perovskite solar cell", Sol. Energy, 237, 29 (2022). CrossRef